2014
DOI: 10.1158/1535-7163.mct-14-0266
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Angiogenesis with a Recombinant CTT Peptide–Endostatin Mimic–Kringle 5 Protein

Abstract: Angiogenesis is required for tumor growth and metastasis, and targeting angiogenesis is a novel anticancer strategy. However, cancer development is a complex multistep process, and single antiangiogenic agents have limited therapeutic efficacy. Here, we report a triple fusion protein, namely CTT peptideendostatin mimic-kringle 5 (AARP), consisting of MMP-2/9-selective inhibitory peptide (CTT peptide) and well-known endogenous antiangiogenic agents (endostatin mimic and kringle 5), which can simultaneously targ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 51 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Testing in a syngeneic mouse model with Lewis lung cancer cell line (LL/2) showed that the fusion peptide with CTT was more effective at retarding tumor growth than clinical endostatin. In vitro and histological testing showed AARP more effective in suppressing endothelial cell activation (proliferation, migration, and tube activation)[201]. MMP-targeting peptides can be used to enhance localization into tumors and increase the efficacy of therapeutic cargo.…”
Section: Strategies For Targetingmentioning
confidence: 99%
“…Testing in a syngeneic mouse model with Lewis lung cancer cell line (LL/2) showed that the fusion peptide with CTT was more effective at retarding tumor growth than clinical endostatin. In vitro and histological testing showed AARP more effective in suppressing endothelial cell activation (proliferation, migration, and tube activation)[201]. MMP-targeting peptides can be used to enhance localization into tumors and increase the efficacy of therapeutic cargo.…”
Section: Strategies For Targetingmentioning
confidence: 99%
“…Accordingly, CTT peptide (CTTHWGFTLC) is an MMP-2 selective inhibitory peptide with reported antiangiogenic activity . CTT is a cyclic peptide (∼1.17 kDa) shown to suppress MMP-2 and significantly block angiogenesis and migration of endothelial and cancerous cells. , Primarily, CTT selectively binds MMP-2 and blocks the endothelial cells from degrading and remodeling the adjacent ECM, leading to the disruption of neovascularization and ultimately tumor growth regression .…”
Section: Introductionmentioning
confidence: 99%